2021
DOI: 10.1007/s10862-021-09868-1
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the Placement of Obsessive-Compulsive Disorder in the Empirical Structure of Psychopathology

Abstract: Committee (5201951338311), and was performed in accordance with the ethics standards as laid down in the 1964 Declaration of Helsinki and its later amendments or comparable ethical standards.Consent to participate: All participants provided written informed consent. Consent for publication:All participants provided consent for their responses to be included in aggregate in a peer-reviewed journal article. Availability of data and material: Data are available upon requestCode availability: All input files are a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 74 publications
6
15
0
Order By: Relevance
“…Consistent with previous findings (Faure & Forbes, 2021; Forbes et al, 2021), our data suggested that OCD features might not be homogeneously associated with the Fear system (e.g., Kotov et al, 2017; Watson, Forbes, et al, 2022). Indeed, the three BOCS scales showed positive and substantial loadings of roughly equal sized with different PCs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous findings (Faure & Forbes, 2021; Forbes et al, 2021), our data suggested that OCD features might not be homogeneously associated with the Fear system (e.g., Kotov et al, 2017; Watson, Forbes, et al, 2022). Indeed, the three BOCS scales showed positive and substantial loadings of roughly equal sized with different PCs.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the three BOCS scales showed positive and substantial loadings of roughly equal sized with different PCs. Notably, all BOCS scales showed standardized loadings >0.40 on PC6_2; this finding was consistent with Faure and Forbes' (2021) study, which provided evidence for a close connection between OCD symptoms and the HiTOP Thought Disorder dimension. At the same time, BOCS Obsession and Severity scale scores showed substantial loadings on the Internalizing component (i.e., PC6_1; Kotov et al, 2017; Watson, Forbes, et al, 2022).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Based on studies of both the clinical phenomenology and personality correlates of OCD, as well as structural analyses of OC symptoms in relation to higher-order psychopathology structure (Faure & Forbes, 2021;Sellbom et al, 2020), we hypothesize that a five-factor solution will yield factors that are recognizable as the PID-5 trait domains and that OC symptoms will most strongly cross-load on the Negative Affect and Psychoticism PID-5 factors. Further, we hypothesize that the OCI-R total score will negatively load on the Disinhibition factor due to the placement of Rigid Perfectionism on the low end of this factor.…”
Section: Current Studymentioning
confidence: 99%